Investigation on Effect of Solution Temperature on The Structure of Cu/Ni Layer in The Electroplating Assisted withParallel Magnetic Field - M Taufiqurrahman; Moh. Toifur; Ishafit Ishafit; Azmi Khusnani (Journal of Aceh Physics Society, 2020)
Tujuan penelitian ini adalah mengidentifikasi pengaruh variasi suhu larutan terhadap struktur lapisan yang terbentuk melalui metode elektroplating. Larutan elektrolit dibuat dengan campuran NiSO4, NiCL2,H3BO3, dan H2O. Elektroplating dilakukan selama 180 s dengan tegangan 4,5 V dan medan magnet 150 G pada arah sejajar permukaan katoda-anoda. Hasil penelitian menunjukkan suhu mempengaruhi ketebalan lapisan, arus listrik, jumlah zat yang terlepas dan terbentuk dan pH larutan. Lapisan paling tebal adalah sampel hasil deposisi pada suhu 40°C dengan ketebalan [(133,8 ± 0,9745)´ 10-5] cm pada pH 4,21. Kemudian yang paling tipis adalah sampel hasil deposisi pada suhu 60°C dengan ketebalan [(59,83 ± 0,6270) x 10-5] cm pada pH 4,18. Ketebalan lapisan yang terbentuk sebanding dengan jumlah zat terlarut dan jumlah arus yang mengalir selama pelapisan berlangsung. The purpose of this study is to identify the effect of temperature variations on the structure of the layers formed through the electroplating method. Electrolyte solution was made with mixture of NiSO4, NiCL2,H3BO3, and H2O. Electroplating was carried out for 180 s on the voltage of 4.5 V and magnetic field parallel to 150 G. The results showed temperature affects the thickness of the layer, electric current, the amount of released and formed substances and the pH of the solution. The thicknest of layer is according to the sample deposited at a temperature of 40°C with a thickness of [(133,8 ± 0,9745)x 10-5] cm at pH of 4.21. Then the thinnest one was according to the sample which was deposited at 60°C with a thickness of [(59,83 ± 0,6270) x 10-5] cm at pH of 4.18. The thickness of the layer is proportional to the amount of solute and the amount of current flowing during the coating. Keywords: Elektroplating, Flim Tipis, Cu/Ni, Suhu Larutan, Magnet Sejajar.